Growth retardation induced by avian leukosis virus subgroup J associated with down-regulated Wnt/β-catenin pathway. (March 2017) - Feng, Weiguo; Zhou, Defang; Meng, Wei; Li, Gen; Zhuang, Pingping; Pan, Zhifang; Wang, Guihua; Cheng, Ziqiang
Abstract: Avian leukosis virus subgroup J (ALV-J), an oncogenic retrovirus, induces growth retardation and neoplasia in chickens, leading to enormous economic losses in poultry industry. Increasing evidences showed several signal pathways involved in ALV-J infection. However, what signaling pathway involved in growth retardation is largely unknown. To explore the possible signaling pathway, we tested the cell proliferation and associated miRNAs in ALV-J infected CEF cells by CCK-8 and Hiseq, respectively. The results showed that cell proliferation was significantly inhibited by ALV-J and three associated miRNAs were identified to target Wnt/β-catenin pathway. To verify the Wnt/β-catenin pathway involved in cell growth retardation, we analyzed the key molecules of Wnt pathway in ALV-J infected CEF cells. Our data demonstrated that protein expression of β-catenin was decreased significantly post ALV-J infection compared with the normal (P < 0.05). The impact of this down-regulation caused low expression of known target genes (Axin2, CyclinD1, Tcf4 and Lef1). Further, to obtain in vivo evidence, we set up an ALV-J infection model. Post 7 weeks infection, ALV-J infected chickens showed significant growth retardation. Subsequent tests showed that the expression of β-catenin, Tcf1, Tcf4, Lef1, Axin2 and CyclinD1 were down-regulated in muscles of growth retardation chickens. Taken together, all data demonstrated that chicken growth retardation caused by ALV-J associated with down-regulated Wnt/β-catenin signaling pathway. Highlights: ALV-J induced growth retardation of CEF cells and chickens. Wnt pathway was down-regulated in ALV-J infection. Growth retardation associated with down-regulated Wnt pathway in ALV-J infected chickens.